2007
DOI: 10.1590/s0100-06832007000500020
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e classificação de plintossolos no Município de Pinheiro-MA

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
1
14
0
18
Order By: Relevance
“…It was observed that the LVe and LAe showed lower silt relative to CXbe referencing the age of the soil. Anjos et al (2007) observed higher silt in "Plintossolos", assigning these levels to weathering processes, which are less significant in some classes, such as the "Cambissolos" and "Plintossolos". Pereira et al (2010) even claim that the amount of silt can also refer to the soil parent material.…”
Section: Physical Attributesmentioning
confidence: 90%
“…It was observed that the LVe and LAe showed lower silt relative to CXbe referencing the age of the soil. Anjos et al (2007) observed higher silt in "Plintossolos", assigning these levels to weathering processes, which are less significant in some classes, such as the "Cambissolos" and "Plintossolos". Pereira et al (2010) even claim that the amount of silt can also refer to the soil parent material.…”
Section: Physical Attributesmentioning
confidence: 90%
“…No horizonte Bwc2 do P4, encontra-se petroplintita, com dimensões de calhaus. A petroplintita é resultante do processo de endurecimento da plintita de forma irreversível, após ciclos sucessivos e alternados de umedecimento e secagem (ANJOS et al, 2007).…”
Section: Atributos Morfológicosunclassified
“…O grau de floculação (GF) observado é < 50% em todos os horizontes e pode ser atribuído à sazonalidade das chuvas (ANJOS et al, 2007) e/ou à oscilação do lençol freático (ZAPAROLI; GASPARETTO, 2010), pois ambos enfraquecem a estabilidade dos agregados do solo, e/ou aos baixos valores dos óxidos de alumínio e de ferro (classes definidas por EMBRAPA, 2013) segundo Vilarinho et al (2013), e/ou a baixos e médios teores de H+Al (classes estabelecidas por TOMÉ JÚNIOR, 1997) conforme Morelli e Ferreira (1987) que são agregantes do solo.…”
Section: Atributos Granulométricosunclassified
See 2 more Smart Citations